Resilience in UK and French Security Strategy: An Anglo-Saxon Bias?. (December 2013) - Joseph, Jonathan
The idea of resilience is increasingly prominent across a wide range of policy areas. This contribution looks at the emergence of resilience in UK security discourse and compares this with the situation in France. It argues that although the term is being debated in France, it is considered to be an Anglo-Saxon import. This article suggests that use of the idea of resilience has more to do with particular forms of governance than with security. It develops this argument through the idea of neoliberal governmentality.